PENDIDlKAN POLITIK BAGI WANITA DA·LAM ERA REFORMASI 8AAT INI - Sri Pujiastuti Sri Pujiastuti (Jurnal Cakrawala Pendidikan, 2001)
In tile present era (Jjo rejorn1s ,11ere is considerable political tension and certainpolitical education transforming current visi()n..\' oj'politics needs to be conducted as aneffort to decrease tile political tenSi()1l. It will present a new vision ofpolitics 10ltgedfor bytJ10se WIlD dearly love peace. In thL\" vision politics will no longer be a rough worldallowing all Ineans14ir or.foul, disavowing any etllics, etc. It will Inake women unafraid totake part in politics so tllat politics will n(J l()nger be a men's w()rld Wilen the people aremore fully aware ofand know more about politics, then they will not be easily made tofight one anotlter, l1lade into blindfarlatics, and made U~\'e ofby tile political elite to gaintlleir lfesires.The transformational political education can be done both formally throughpedagogy alld informally tJlrougJl androgynous tllinking and. by nleans ofthe mass media,botll electronic and printed. TIle education uses a critical paradigm, i.e., a paradigm withtIle purpose offundanlentally tran5forming a system and structure.Tile educational material can consist oftIle following: (1) tile state and the statesystem, (2) tIle people's political rights, (3) political parties andprqfiles ofpoliticalpartiesparticipating in general elections, (4) general elections and tlleir ~ystems, and (5) basic11uman rig/2Is, civil'and political rights, and androgynous leaderS/lip.